Electrophysiological and functional responses to paired associative brain stimulation - McNickle, Emmet (Trinity College (Dublin, Ireland). School of Psychology, 2016)
Non invasive brain stimulation (NIBS) methods have exploded in popularity over the last two decades. Despite exhibiting an exponential growth in the number of publications over that period, the field of NIBS research remains somewhat distant from either a sound mechanistic understanding of the effect that these techniques have, or from a clinically useful application of these approaches to therapeutic targets. Modem NIBS methods were developed from stimulation studies on animal models and reduced preparations. These origins have played a key role in shaping how the field has attempted to characterise the underlying mechanisms of action. This heritage has also influenced expectations of what may be practically achieved using NIBS. The foci of this thesis are twofold. The first theme looks at whether the mechanisms observed in reduced preparation experiments can necessarily be extrapolated to the level of intact human systems that are more complex by many orders of magnitude. The second theme is an examination of whether the electrophysiological outcome measures used in stimulation studies in the human motor system are a useful predictor of behaviourally relevant change.
Keywords: Psychology, Ph.D.; PhD Trinity College Dublin, 2016